The impact of new regulations on earnings management among Malaysian listed firms - Abdullah, Shamsul Nahar; Che A Halim, Nur Fajrina; Puat Nelson, Sherliza (2014)
We examine the impact of the establishment of the Audit Oversight Board (AOB) on audit effort and the effect of the introduction of provisions 317A and 320A of the Capital Markets and Services Act (CMSA) and earnings management. Thus, auditors have to put in more effort, which requires them to increase audit fees to compensate the increase in hours spent on an engagement. As for Sections 317A and 320A of the CMSA, the objective is to ensure the independent directors are more effective in discharging their monitoring roles. The data for the study is obtained from secondary data (annual reports). The final data sample comprises 2,124 observations collected from the annual reports of 708 firms for three years from 2009–2011, which covers the periods before and after the establishment of the AOB. The results indicate that there is an increase in audit effort from pre- to post-AOB. The regression analyses also reveal the role of board independence in reducing earnings management after the new regime was enforced.